Does substance misuse moderate the relationship between criminal thinking and recidivism?. Issue 1 (January 2015) - Caudy, Michael S.; Folk, Johanna B.; Stuewig, Jeffrey B.; Wooditch, Alese; Martinez, Andres; Maass, Stephanie; Tangney, June P.; Taxman, Faye S.
Abstract: Purpose: Some differential intervention frameworks contend that substance use is less robustly related to recidivism outcomes than other criminogenic needs such as criminal thinking. The current study tested the hypothesis that substance use disorder severity moderates the relationship between criminal thinking and recidivism. Methods: The study utilized two independent criminal justice samples. Study 1 included 226 drug-involved probationers. Study 2 included 337 jail inmates with varying levels of substance use disorder severity. Logistic regression was employed to test the main and interactive effects of criminal thinking and substance use on multiple dichotomous indicators of recidivism. Results: Bivariate analyses revealed a significant correlation between criminal thinking and recidivism in the jail sample ( r  = .18, p  < .05) but no significant relationship in the probation sample. Logistic regressions revealed that SUD symptoms moderated the relationship between criminal thinking and recidivism in the jail-based sample ( B  = -.58, p  < .05). A significant moderation effect was not observed in the probation sample. Conclusions: Study findings indicate that substance use disorder symptoms moderate the strength of the association between criminal thinking and recidivism. These findings demonstrate the need for further research into the interaction between various dynamic risk factors. Highlights: Criminal thinking and substance use predicted recidivism in a jail sample Neither construct predicted recidivism in a drug-involved probation sample SUD severity moderated the association between criminal thinking and recidivism Findings varied across measures of recidivism Identifying moderators is important for establishing what works for whom